Application of ethnomathematical materials for teaching and learning in university students - Meza-Paucar, Toño (2019)
The research aimed to design educational materials according to the ethno of their context, to apply in the teaching and learning of mathematics, where this method must be combined with other active methods according to nature, for this purpose the design was quasi-experimental with the application of a pre test, process and post test; formed by the students of the III and V cycle of the Professional School of Primary Education of the National University Hermilio Valdizán - Obas, enrolled in the academic year 2017, in the first experimental group the ethnomathematical materials designed in the research were used, while in the second control group, the conventional approach dictated by the Ministry of Education. For this, a diagnosis was made in the public institutions of the Obas district, where the pedagogical instruments were applied, processed, verified and analyzed and thus obtain the following results in the post-test, the median or 50% of the students of the experimental group they scored higher than 14, in parallel 50% of the students in the control group scored lower than 14 and the other 50% scored higher than 11. Therefore, it is concluded that it positively influences the teaching and learning of mathematics , in the students.